2015
DOI: 10.1002/pd.4582
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of prenatal ultrasound in determining the type of orofacial cleft

Abstract: Prenatal ultrasound is accurate in assessing the types of orofacial clefts in a large majority of the cases and is completely accurate in distinguishing between unilateral and bilateral clefts. This study indicates that it is a reliable technique to assess the cleft type, which is important for counseling future parents. Although, the clinician should be aware of the fact that a cleft palate is easily missed, and subsequently, underestimation of cleft extend is frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
2
28
0
2
Order By: Relevance
“…Abnormalities of the palate are frequently missed on ultrasound evaluation . Even when CL/CLA is already detected, diagnosing palate involvement is often ambiguous prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the palate are frequently missed on ultrasound evaluation . Even when CL/CLA is already detected, diagnosing palate involvement is often ambiguous prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…Orofacial clefts are one of the most common congenital craniofacial abnormalities . Ultrasonography (US) is presently the routine modality for the antenatal diagnosis of facial malformations . When an orofacial cleft is suspected on US screening, an accurate classification of the condition is essential, as the risk for associated structural and genetic anomalies is dependent on the cleft type .…”
Section: Introductionmentioning
confidence: 99%
“…The 3‐D geometrical analysis can visualize all relevant anatomical landmarks, such as upper lip outline and quantification of facial asymmetry . However, this method is not suitable for evaluating of the palate, hence a fetal CP can be easily missed by US . A review in 2017 revealed that the detection rate of US for fetal CP was only 0‐1.4% …”
Section: Introductionmentioning
confidence: 99%
“…Gebeliğin ilk tanısından itibaren takip amacıyla kullanıldığı gibi, 16-20 haftalar arasında anomali taraması amacıyla ayrıca gerçekleştirilmektedir. Özellikle ileri anne yaşı, pozitif aile öyküsü, diyabetik anne çocuğu olmak, yüksek ateşli hastalık geçirilmesi, riskli ilaçların kullanımı, annenin alkol-sigara kullanımı ve radyasyona maruziyet gibi durumların varlığında yüksek risk taşıyan popülasyonda bu amaçla ultrasonografinin kullanımı daha da anlam kazanmaktadır (24) .…”
Section: Discussionunclassified